Decompressive craniectomy: a meta-analysis of influences on intracranial pressure and cerebral perfusion pressure in the treatment of traumatic brain injury A review - Bor-Seng-Shu, Edson (2012)
Object. in recent years, the role of decompressive craniectomy for the treatment of traumatic brain injury (TB!) in patients with refractory intracranial hypertension has been the subject of several studies. the purpose of this review was to evaluate the contribution of decompressive craniectomy in reducing intracranial pressure (ICP) and increasing cerebral perfusion pressure (CPP) in these patients.Methods. Comprehensive literature searches were performed for articles related to the effects of decompressive craniectomy on ICP and CPP in patients with TBI. Inclusion criteria were as follows: 1) published manuscripts, 2) original articles of any study design except case reports, 3) patients with refractory elevated ICP due to traumatic brain swelling, 4) decompressive craniectomy as a type of intervention, and 5) availability of pre- and postoperative ICP and/or CPP data. Primary outcomes were ICP decrease and/or CPP increase for assessing the efficacy of decompressive craniectomy. the secondary outcome was the persistence of reduced ICP 24 and 48 hours after the operation.Results. Postoperative ICP values were significantly lower than preoperative values immediately after decompressive craniectomy (weighted mean difference [WMD] -17.59 mm Hg, 95% CI -23.45 to -11.73, p < 0.00001), 24 hours after (WMD -14.27 mm Hg, 95% Cl -24.13 to -4.41, p < 0.00001), and 48 hours after (WMD -12.69 mm Hg, 95% Cl -22.99 to -2.39, p < 0.0001). Postoperative CPP was significantly higher than preoperative values (WMD 7.37 mm Hg, 95% Cl 2.32 to 12.42, p < 0.0001).Conclusions. Decompressive craniectomy can effectively decrease ICP and increase CPP in patients with TBI and refractory elevated ICP. Further studies are necessary to define the group of patients that can benefit most from this procedure. (http://thejns.org/doi/abs/10.3171/2012.6.JNS101400)